6x-6-4x=6x-5

Simple and best practice solution for 6x-6-4x=6x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-6-4x=6x-5 equation:


Simplifying
6x + -6 + -4x = 6x + -5

Reorder the terms:
-6 + 6x + -4x = 6x + -5

Combine like terms: 6x + -4x = 2x
-6 + 2x = 6x + -5

Reorder the terms:
-6 + 2x = -5 + 6x

Solving
-6 + 2x = -5 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-6 + 2x + -6x = -5 + 6x + -6x

Combine like terms: 2x + -6x = -4x
-6 + -4x = -5 + 6x + -6x

Combine like terms: 6x + -6x = 0
-6 + -4x = -5 + 0
-6 + -4x = -5

Add '6' to each side of the equation.
-6 + 6 + -4x = -5 + 6

Combine like terms: -6 + 6 = 0
0 + -4x = -5 + 6
-4x = -5 + 6

Combine like terms: -5 + 6 = 1
-4x = 1

Divide each side by '-4'.
x = -0.25

Simplifying
x = -0.25

See similar equations:

| =-14-6v | | 9b=81 | | -x+4x=18 | | 2(2x-138)=x+24 | | 2x+3(.25x)=55 | | 4x+-8=18 | | 5f=-50 | | 4-6+5x= | | 4=-9 | | -7-(-8)=x | | 10.3x-32=-7x+28 | | (2x-(-4))(3x+(-2))=3-(5-3x)(2x+3) | | =h(a+b) | | -7-6=x | | 10x-11x+3=0 | | -9-3=x | | n-9=-42 | | -5(6m-3)=38-7m | | -10+4x=-42 | | 0.88=log(x) | | 2(9x+631)=2x+270 | | .88=log(x) | | 1-5b-4b=10 | | 11z=-100 | | 3n-9+3=24 | | 3(14-4y)-5y=-9 | | 6y+5=10y-1 | | 12k+14=10k-2k-7 | | -3(x+4)+16= | | J-8=-5 | | 10x-8=31.5 | | 2(2x-11)=2x |

Equations solver categories